Colorectal Cancer Safety Net: Is It Catching Patients Appropriately?. Issue 1 (January 2018) - Althans, Alison R.; Brady, Justin T.; Times, Melissa L.; Keller, Deborah S.; Harvey, Alexis R.; Kelly, Molly E.; Patel, Nilam D.; Steele, Scott R.
Abstract : BACKGROUND: Disparities in access to colorectal cancer care are multifactorial and are affected by socioeconomic elements. Uninsured and Medicaid patients present with advanced stage disease and have worse outcomes compared with similar privately insured patients. Safety net hospitals are a major care provider to this vulnerable population. Few studies have evaluated outcomes for safety net hospitals compared with private institutions in colorectal cancer. OBJECTIVE: The purpose of this study was to compare demographics, screening rates, presentation stage, and survival rates between a safety net hospital and a tertiary care center. DESIGN: Comparative review of patients at 2 institutions in the same metropolitan area were conducted. SETTINGS: The study included colorectal cancer care delivered either at 1 safety net hospital or 1 private tertiary care center in the same city from 2010 to 2016. PATIENTS: A total of 350 patients with colorectal cancer from each hospital were evaluated. MAIN OUTCOME MEASURES: Overall survival across hospital systems was measured. RESULTS: The safety net hospital had significantly more uninsured and Medicaid patients (46% vs 13%; p < 0.001) and a significantly lower median household income than the tertiary care center (39, 299 vs 49, 741; p < 0.0001). At initial presentation, a similar percentage of patients at each hospital presented with stage IV disease (26% vs 20%; p = 0.06). For those undergoing resection, final pathologic stage distribution was similar across groups ( p = 0.10). After a comparable median follow-up period (26.6 mo for safety net hospital vs 29.2 mo for tertiary care center), log-rank test for overall survival favored the safety net hospital ( p = 0.05); disease-free survival was similar between hospitals ( p = 0.40). LIMITATIONS: This was a retrospective review, reporting from medical charts. CONCLUSIONS: Our results support the value of safety net hospitals for providing quality colorectal cancer care, with survival and recurrence outcomes equivalent or improved compared with a local tertiary care center. Because safety net hospitals can provide equivalent outcomes despite socioeconomic inequalities and financial constraints, emphasis should be focused on ensuring that adequate funding for these institutions continues. SeeVideo Abstract athttp://links.lww.com/DCR/A454 .